Factors associated with anxiety and depression among elderly living in old aged homes in Kathmandu Valley. - Timalsina, Rekha (2013)
ABSTRACT: The elderly people not only face physical problems as they are age, they also experience mental health related problems. The main objective of the study was to identify the level of anxiety and depression and the factors associated with them among elderly living in 10 old age homes in Kathmandu Valley of Nepal. The cross-sectional descriptive analytical study design along with case study was used among 173 respondents who were selected by purposive sampling. Interview was carried out using socio-demographic and other variables related tool, the partially adopted coping checklist, HAM-A tool and the GDS. The data analysis was done by using Epidata software and SPSS version 16. Descriptive statistics, and inferential statistics, viz., chi square test and odds ratio were calculated. Regarding anxiety, the findings reveal that according to HAM-A Tool, 56 (32.4%) respondents had anxiety. Out of them, 36 (20.8%), 11 (6.4%) and 9 (5.2%) respondents had mild, moderate and severe anxiety respectively. Out of 45 male respondents, 10 (22.2%) had anxiety as compared to 45 (35.2%) out of 128 female respondents. The respondents who had chronic physical health problems (CPHP), worries, dissatisfaction with old aged homes and even those who used coping strategies like visiting different places, were found to have anxiety. Regarding depression, 126 (72.8%) respondents had depression. Out of them, according to GDS, 98 (56.6%) and 28 (16.2%) respondents had mild and severe depression respectively. This study also reveals that out of 45 male respondents, 28 (62.2%) had depression as compared to 98 (76.6%) out of 128 female respondents. The respondents who had CPHP; different types of worries like financial security, lack of social relation, lack of favorite activities, fear of future and dissatisfaction with environment of the elderly homes; feeling of stress and even those who used coping strategies like self blame were found to have depression. Based on these findings, it can be suggested that new coping strategies as well as mind diversional activities should be sought for preventing depression among elderly living in old age homes. Key Words: Factors Associated with Elderly Anxiety and Depression